Correlates of Self-Rated Health among Muslims in the United States. Issue 4 (October 2015) - Hodge, David R.; Zidan, Tarek; Husain, Altaf; Hong, Philip Young P.
Despite the large and growing population of Muslims in the United States, a paucity of research exists on the variables that may impact health status among members of this distinct cultural group. We address the lack of research by identifying correlates of self-rated health among a community sample of Muslims in the United States (N = 269). We examine the effects of demographic characteristics, health behaviors, psychological health, and contextual factors in the form of discrimination and spirituality. The results of our sequential logistic regression indicate that Muslims who were younger, married, had a graduate degree, and prayed more frequently were more likely to report higher levels of self-rated health. Conversely, respondents who reported clinically significant levels of depressive symptoms and those who reported being singled out by law enforcement as a result of being a Muslim were more likely to report poorer self-rated health. We conclude by discussing the implications of the results for social work practice with Muslims.